2014
DOI: 10.1074/jbc.m114.590711
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of the Topoisomerase Domain of Methanopyrus kandleri Topoisomerase V

Abstract: Background: Topoisomerase V is a unique enzyme and the sole member of the IC subtype of type I topoisomerases. Results: We probed the role of several amino acids comprising the topoisomerase active site to elucidate their role in catalysis. Conclusion:The work reveals the role of several amino acids and suggests interesting parallels with type IB topoisomerases. Significance: The results expand our understanding of this new subtype of topoisomerases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 41 publications
(88 reference statements)
3
17
0
Order By: Relevance
“…Finally, Lys218 is not making contacts with the DNA but is close enough to Tyr226 that it could contact the P0 phosphate. Thus, all residues that have been involved in cleavage and religation are positioned in a manner consistent with their previously assigned roles (Rajan et al, 2014).…”
Section: Active Sitesupporting
confidence: 69%
See 2 more Smart Citations
“…Finally, Lys218 is not making contacts with the DNA but is close enough to Tyr226 that it could contact the P0 phosphate. Thus, all residues that have been involved in cleavage and religation are positioned in a manner consistent with their previously assigned roles (Rajan et al, 2014).…”
Section: Active Sitesupporting
confidence: 69%
“…The residues forming the topoisomerase active site were recognized based on structural and biochemical observations (Rajan et al, 2014;Taneja et al, 2006). The complex structure confirms that Arg131, Arg143, His200, Glu215, Lys218 and Tyr226 are involved in interacting with DNA and helps understand their role in the DNA cleavage/religation reaction.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Type IC topoisomerases comprise the most recently identified family of topoisomerases ( 6 , 7 ). Although they have many characteristics in common with type IB enzymes ( 8 10 ), the structure elucidation of a 61 kDa fragment of Methanopyrus kandleri Topoisomerase-V (Topo-V) ( 7 ) revealed that they form a distinct sub-type. In addition to relaxation activity, type IC enzymes show DNA repair activity ( 11 , 12 ), suggesting a close relationship between these two essential functions in hyperthermophiles.…”
Section: Introductionmentioning
confidence: 99%
“…Topo-V shows a modular structure with a 30 kDa topoisomerase domain followed by 24 helix-hairpin-helix (HhH) motifs arranged as 12 tandem (HhH) 2 domains ( 7 , 11 ). The topoisomerase domain has no sequence or structural similarity to any other topoisomerase ( 7 ), the active site is well mapped and biochemical studies have shown that the cleavage and religation reactions are similar to the ones employed by type IB enzymes ( 8 ). In addition, single molecule studies have shown that Topo-V relaxes DNA by controlled rotation or swiveling, again in a similar manner to type IB topoisomerases ( 10 ).…”
Section: Introductionmentioning
confidence: 99%